Creating English Articles about Kayutangan Heritage for Tugu Jatim - Kautsar, Rizal; Setiawan, Ardian Wahyu; Sakinah, Yanik Lalinas (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research aimed to develop seven English articles about Kayutangan Heritage for Tugu Jatim to address the lack of English tourism content on the Tugu Jatim website. The purpose of this research was to increase the number of English articles on the Tugu Jatim’s tourism channel and align with Tugu Jatim's "Merawat Jawa Timur" slogan. This research utilized the analysis, design, development, implementation, and evaluation stages of ADDIE theory, an adaptation of the Design and Development Research model proposed by Richey Rita C. and Klein (2014). Data collection methods included published article and SEO content analysis, article design, interviews, and expert validation. This research resulted in six published articles of the seven article drafts in total. The six articles were published after matching with the article writing guideline and worth publishing. There was one article that was not published due to its non-SEO-friendly keyword usage, which made the title, lead, and conclusion irrelevant. The findings emphasize the importance of conducting SEO keyword research and creating interesting content to ensure article readability. The subsequent research was expected to develop SEO-friendly articles that contain local tourist destination promotion.